Acute Intoxications and Fatalities From Illicit Fentanyl and Analogues: An Update. Issue 1 (February 2018) - Pichini, Simona; Solimini, Renata; Berretta, Paolo; Pacifici, Roberta; Busardò, Francesco Paolo
Abstract : Abstract: Illicit fentanyl and its analogues are very dangerous synthetic opioids, with high abuse potential and severe adverse effects including coma and death. They are used as adulterants in street heroin, cocaine, and methamphetamine, or as heroin substitutes sold to unaware users with a high risk of overdoses. Fentanyl and its analogues have also been identified in counterfeit medicinal products, such as oxycodone, hydrocodone, and alprazolam tablets, or as components of speedball mixtures together with cocaine or other stimulants. In recent years, a number of epidemics involving acute intoxications and deaths related to illicit fentanyl or its analogues have occurred in the United States, Europe, Canada, Australia, and Japan. In several cases, fatalities involved polysubstance use. A review of the most recent case reports or case series of acute intoxications and fatalities involving illicit fentanyl and its newest analogues is herein provided, together with the available information on intoxication symptoms, eventual death cause, and metabolites detected in different biological fluids and reported concentrations.